The 1000 Ḥāfiẓ Program as a Living Qur’an Practice: A Socio-Religious Study in Pasaman Regency, West Sumatra - Rona Hamdani; Ahmad Zaky; Muhardika Muhardika; Muhammad Taufiq (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2026)
The tradition of memorizing the Qur’an (Taḥfiẓ) represents one of the forms of internalization and actualization of Qur’anic values in the life of Muslim communities. Pasaman Regency, West Sumatra, initiated the 1000 Ḥāfiẓ Program as a strategic effort to instill Qur’anic values among the younger generation while strengthening the religious culture of the community. This study aims to analyze the program from the perspective of Living Qur’an, an approach that examines how the Qur’an is practiced, experienced, and internalized within the social life of society. Using a qualitative method with phenomenological and sociological approaches, this article explores the dynamics of Taḥfiẓ practices within the socio-religious context of the Pasaman community. The findings indicate that the 1000 Ḥāfiẓ Program represents the Qur’an as a living text, a sacred text that is not merely read and memorized but also actualized in the formation of character, the strengthening of social control, and the construction of the community’s religious identity. Through Taḥfiẓ activities, Qur’anic instruction, and the development of a religious culture within educational institutions and society, the Qur’an functions as a living value that shapes socio-religious practices. In addition to producing Qur’an memorizers, the program also strengthens social morality and the Islamic identity of the Pasaman community. Therefore, the sustainability of this program should continue to be supported through synergy among local government, educational institutions, and the wider community so that Qur’anic values remain alive and functional in social reality.